2022
DOI: 10.1111/jth.15637
|View full text |Cite
|
Sign up to set email alerts
|

Alternate‐day dosing of caplacizumab for immune‐mediated thrombotic thrombocytopenic purpura

Abstract: Background:The anti-von Willebrand factor (VWF) nanobody caplacizumab directly prevents the fatal microthrombi formation in immune-mediated thrombotic thrombocytopenic purpura (iTTP), thereby adding a new therapeutic principle to the treatment of this disorder. However, real-world treatment modalities beyond clinical trials remain heterogeneous.Methods: Here, we describe the risks and benefits of an alternate-day dosing regimen for caplacizumab by thoroughly analyzing the timing and outcome of this approach in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 17 publications
(51 reference statements)
0
13
0
Order By: Relevance
“…In this case, alternate day dosing of caplacizumab is sufficient to prevent exacerbations and reduces treatment costs. 147 In summary, the current data suggest that in patients with suspected or proven TTP, a protocol consisting of an early frontline start of caplacizumab (with or without plasma exchange), early addition of rituximab to shorten time to ADAMTS13 recovery, and continuation of daily caplacizumab until ADAMTS13 activity consistently exceeds 10% with the possibility to switch to alternate day dosing provides a reasonable individualized, pathophysiology-based treatment with low rates of exacerbation and mortality at economically acceptable costs.…”
Section: Prolongation Of Caplacizumab Dosing Intervalsmentioning
confidence: 80%
See 2 more Smart Citations
“…In this case, alternate day dosing of caplacizumab is sufficient to prevent exacerbations and reduces treatment costs. 147 In summary, the current data suggest that in patients with suspected or proven TTP, a protocol consisting of an early frontline start of caplacizumab (with or without plasma exchange), early addition of rituximab to shorten time to ADAMTS13 recovery, and continuation of daily caplacizumab until ADAMTS13 activity consistently exceeds 10% with the possibility to switch to alternate day dosing provides a reasonable individualized, pathophysiology-based treatment with low rates of exacerbation and mortality at economically acceptable costs.…”
Section: Prolongation Of Caplacizumab Dosing Intervalsmentioning
confidence: 80%
“…In addition, the steep learning curve with caplacizumab enabled considerations on individualized, pathophysiology-based therapy, not adhering to the strict labeling. [143][144][145][146][147][148][149] Today, caplacizumab has been established as the first-line therapy of immune TTP in many centers as recommended in current guidelines. 51,88,94,144,145,150 Milestone 5: Individualized TTP Treatment Considering all these fundamental innovations in TTP management, a redefinition of outcome parameters was necessary.…”
Section: Milestone 4: Caplacizumabmentioning
confidence: 99%
See 1 more Smart Citation
“…Caplacizumab should be started before PE and then continue daily until 30 days after PE completion 13 . Caplacizumab is an expensive drug (approximate 270 000 dollars per treatment) and methods to individualize treatment are being investigated, such as alternative day dosing or reducing the initial course 17 . Volker et al found that monitoring ADAMTS13 activity allowed clinicians to individualize treatment by shortening or extending caplacizumab duration with successful outcomes 18 .…”
Section: Thrombotic Thrombocytopenic Purpura Incidence and Pathogenesismentioning
confidence: 99%
“…13 Caplacizumab is an expensive drug (approximate 270 000 dollars per treatment) and methods to individualize treatment are being investigated, such as alternative day dosing or reducing the initial course. 17 Volker et al found that monitoring ADAMTS13 activity allowed clinicians to individualize treatment by shortening or extending caplacizumab duration with successful outcomes. 18 The study concluded that most aTTP patients could have a shorter duration of caplacizumab treatment but 20% would benefit from a longer duration.…”
Section: Acute Periodmentioning
confidence: 99%